2014
DOI: 10.1080/10426914.2014.984203
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Design of Nickel-Based Superalloys Using Data-Driven Genetic Algorithms and Related Strategies

Abstract: Data-driven models were constructed for the mechanical properties of multi-component Ni-based superalloys, based on systematically planned, limited experimental data using a number of evolutionary approaches. Novel alloy design was carried out by optimizing two conflicting requirements of maximizing tensile stress and time-to-rupture using a genetic algorithm-based multi-objective optimization method. The procedure resulted in a number of optimized alloys having superior properties. The results were corroborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 43 publications
(87 reference statements)
0
19
0
Order By: Relevance
“…A GA is used as it enables random but directional iterative optimization of the design parameters [35]. It has been successfully applied in many material research related problems [13,42,58,87]. Unlike the gradient-based or the other grid search algorithms, each GA process requires a significant number of iterations to converge but it is efficient for multi-objective, multi-dimensional optimizations [35,75].…”
Section: Optimization By Genetic Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…A GA is used as it enables random but directional iterative optimization of the design parameters [35]. It has been successfully applied in many material research related problems [13,42,58,87]. Unlike the gradient-based or the other grid search algorithms, each GA process requires a significant number of iterations to converge but it is efficient for multi-objective, multi-dimensional optimizations [35,75].…”
Section: Optimization By Genetic Algorithmmentioning
confidence: 99%
“…A variety of efforts have been made to design efficient algorithms, including genetic algorithms (GA) coupled with CALPHAD-based tools [58,86,87], atomistic simulations [13,31,40], and data-driven approaches [42,55,78,102]. The goal of this work is to develop a platform that integrates federated experimental and computational data repositories with CALPHAD-based tools and mechanistic property models to predict materials behavior and enable materials design using a GA. A model ternary Ni-Al-Cr alloy is chosen to demonstrate this platform.…”
Section: Introductionmentioning
confidence: 99%
“…Integrated Computational Materials Engineering (ICME) approach [8] and materials genome initiative highlighted the importance and growing application of computational tools in the design of new alloys. In recent years, various data-driven techniques combined with evolutionary approaches [9] have been successfully implemented in direct alloy design [9][10][11][12][13][14] and inverse alloy design [15] and in improving thermodynamic databases such as Thermocalc [16] for alloy development. Jha et al [12,13] demonstrated the scope of use of these databases for designing Ni-based superalloy and Rettig et al [14] performed a few experiments to confirm his findings.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In recent years, various data-driven techniques combined with evolutionary approaches [9] have been successfully implemented in direct alloy design [9][10][11][12][13][14] and inverse alloy design [15] and in improving thermodynamic databases such as Thermocalc [16] for alloy development. Jha et al [12,13] demonstrated the scope of use of these databases for designing Ni-based superalloy and Rettig et al [14] performed a few experiments to confirm his findings. Data mining approaches such as Principal Component Analysis (PCA) and Partial Least Square (PLS) regression have been successfully used in designing new alloys [17,18].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In recent decades, in order to deal with the complicated training problem of the ANN, many metaheuristic optimization algorithms, such as Simulated Annealing (SA) [26,27], GA [30], and PSO [31], have been utilized to optimize the weights and biases of ANN. Besides, the recently proposed EvoNN [32,33] algorithm, which utilizes the multiobjective optimization technique in the training process of a feedforward neural network, ensures correct neural training by working out a Pareto tradeoff between the accuracy of the training and the complexity of the network. In this section, we use our BSODE algorithm to adjust connection weights and biases of ANN.…”
Section: Applications Of Ann Using Bsodementioning
confidence: 99%